(untitled) (Texas Journal of Medical Science, 2024)
This article presents the potential use of precautionary measures and good hygiene as the basis for protection against infection. In infection prevention courses at tertiary health care institutions. Additional precautions include wearing masks, gloves and aprons, especially where contact transmission is possible. These simple but important principles will help protect your health and the health of those around you from various diseases